(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The significance of Bloom’s Taxonomy in enhancing English language listening skills is covered in this article. While Bloom’s Taxonomy is widely regarded as one of the most effective teaching approaches in English classrooms, there is a dearth of knowledge and resources on its application in improving listening comprehension. The function of this approach in involving teaching and learning will be examined in this paper.